Administration of Phosphonate Inhibitors of Dehydrogenases of 2-Oxoglutarate and 2-Oxoadipate to Rats Elicits Target-Specific Metabolic and Physiological Responses - Bunik, Victoria I.; Artiukhov, Artem V.; Kazantsev, Alexey V.; Aleshin, Vasily A.; Boyko, Alexandra I.; Ksenofontov, Alexander L.; Lukashev, Nikolay V.; Graf, Anastasia V. (Frontiers in Chemistry, 2022)
In vitro and in cell cultures, succinyl phosphonate (SP) and adipoyl phosphonate (AP) selectively target dehydrogenases of 2-oxoglutarate (OGDH, encoded by OGDH/OGDHL) and 2-oxoadipate (OADH, encoded by DHTKD1), respectively. To assess the selectivity in animals, effects of SP, AP and their membrane-penetrating triethyl esters (TESP and TEAP) on the rat brain metabolism and animal physiology are compared. Opposite effects of the OGDH and OADH inhibitors on activities of OGDH, malate dehydrogenase, glutamine synthetase, and levels of glutamate, lysine, citrulline, carnosine, are shown to result in distinct physiological responses. ECG is changed by AP/TEAP, whereas anxiety is increased by SP/TESP. Potential role of the ester moiety in the uncharged precursors of the 2-oxo acid dehydrogenase inhibitors is estimated. TMAP is shown to be less efficient than TEAP, in agreement to a lower lipophilicity of TMAP vs TEAP. Non-monotonous metabolic and physiological impacts of increasing OADH inhibition are revealed. Compared to the non-treated animals, strong inhibition of OADH decreases levels of tryptophan and beta-aminoisobutyrate, activities of malate dehydrogenase and pyruvate dehydrogenase, increasing R-R interval of ECG. Thus, both metabolic and physiological actions of the OADH-directed inhibitors AP/TEAP are different from those of the OGDH-directed inhibitors SP/TESP, with the ethyl ester more efficient than methyl ester.